Effectiveness of messaging apps in emergency room-online survey study - Ghodke, Ashok; Gunjotikar, Aditya; Vatkar, Arvind; Kale, Sachin; Yadav, Praveen; Mandal, Shobhan; Verma, Ashmit; Sonali; Kale, Sachiti Sachin (International Journal of Research in Orthopaedics, 2023)
Background: Medical professionals communicate effectively and conveniently using mobile communication applications (Apps). With clinical details being transmitted quickly among multidisciplinary teams, the potential improvements in patient care and education are significant. However, there are also moral and legal concerns with sharing patient data in this manner. This study aimed to quantify and categorize how often medical staff members used communication apps in clinical settings, their role in patient care, their knowledge of and attitudes toward safety, and the main advantages, potential drawbacks, and policy implications. Methods: A 16-question survey with an anonymous response was distributed to our 1500 bedded hospital’s medical staff. The study gathered information on the demographics of the respondents, how they used communication apps in clinical settings, how they felt about such apps, how safe they thought their data was, and why they chose one app over another. The study period was January to March 2023. Results: From students to consultants, communication apps are widely utilized with WhatsApp being the most popular one. Although all respondents thought these apps were useful for swiftly exchanging information in a clinical context, they were all concerned about the privacy consequences. Overall, 62.5% use WhatsApp in the ER, and 70.8% found that it has helped reduce the communication gap between junior and senior orthopaedic surgeons. Conclusions: Messaging apps help medical professionals communicate more effectively, but their use poses compliance difficulties, particularly with privacy laws. Hence, a user-friendly design and privacy-compliant must be given top priority when creating apps.